HUBUNGAN ANTARA AKTIVITAS FISIK DENGAN DEPRESI PADA LANSIA WANITA DI KOMUNITAS DAHLIA SENJA LIMO DEPOK - Wulan Pragusthasari (2023)
Background: As the elderly population increases, it can have both negative and positive impacts. In addition, decreased physical activity can increase the risk of depression. Depression among the elderly often goes undetected due to decreased executive function and is seen as a process of aging that results in worsening health status, and low quality of life. The purpose of this study was conducted to determine the relationship between physical activity and depression in the Dahlia Senja Women's Elderly Community Limo Depok. Design: This study used a cross- sectional study method with a method of measuring physical activity of the elderly using the International Physical Activity Questionnaire- Short Form (IPAQ-SF) and a method of measuring depression in the elderly using the Geriatric Depression Scale (GDS) questionnaire. The sample in this study were elderly women in the Dahlia Senja Community totaling 40 people. Results: This study says that 45% of physical activity is included in the moderate category and depression is included in the normal limit of 55% in elderly women at the Dahlia Senja Community. The p value = 0.352 with p>0.05 and it can be concluded that there is no relationship between physical activity and depression in elderly women at the Dahlia Senja Community Limo Depok. Keywords: Depression, Physical Activity, Elderly